The films of Mary Harron. - Barrett, Kyle (Edinburgh University Press, 2021)
Offers the first first book-length study of Mary Harron's career and works.
Description based upon print version of record.
Keywords: Harron, Mary -- Criticism and interpretation.; Harron, Mary; Motion picture producers and directors -- Canada.; Women motion picture producers and directors -- Canada.; Producteurs et réalisateurs de cinéma -- Canada.; Productrices et réalisatrices de cinéma -- Canada.; Motion picture producers and directors; Women motion picture producers and directors; Canada; Criticism, interpretation, etc.